Waist-height ratio: How well does it predict glucose intolerance and systemic hypertension?. (December 2019) - Lawal, Yakubu; Bello, Fatima; Anumah, F.E.; Bakari, A.G.
Abstract: Aim: The aim of this study is to assess whether WHtR is a better predictor of glucose intolerance and systemic hypertension than some other obesity indices. Methods: This is a cross-sectional observational study among four hundred (4 0 0) participants in a Northern Nigerian population. Four (4) participants were eventually excluded due to incomplete data, therefore data from three hundred and ninety six (3 9 6) participants were used in the final analysis. The study assessed whether WHtR is a better predictor of glucose intolerance and systemic hypertension compared to some other obesity indices. Participants were recruited after due consent, then bio-data, blood pressure levels, and some anthropometric measurements were obtained. Subsequently, plasma glucose levels (fasting [FPG] and 2-hour post 75 g glucose load [2HrPPG]) were measured. Data was entered into Microsoft Excel, then analyzed using IBM SPSS version 23. Results: Data from three hundred and ninety six (3 9 6) participants (4 excluded due to incomplete details) were analyzed. Logistic regression of obesity indices showed that WHtR was the best predictor of glucose intolerance with odds ratio (OD) of 20.74 (CI 2.80-155, p < 0.001), followed by WC with OD of 1.89 (CI 1.83-3.94, p < 0.001), then WHR with OD of 1.69 (CI 1.06-8.22, p = 0.009). The least but significant predictor of glucose intolerance was BMI with odds ratio of 1.12 (CI 1.06-3.18, p < 0.001). Furthermore, logistic regression of obesity indices showed that WHtR was the strongest predictor of systemic hypertension with OD of 2.32 (CI 4.85-14.96, p < 0.001), followed by BMI (OD 1.99, CI 1.96-2.05, p = 0.031), then WC (OD 1.95, CI 1.90-1.99, p = 0.020). The weakest predictor of systemic hypertension was WHR (OD 1.26, CI 0.04-1.88, p = 0.181). Conclusion: WHtR had the highest predictive power for both glucose intolerance and systemic hypertension compared to BMI, WC, and WHR.